An Investigation of Consumer Online Trust and Purchase-Repurchase Intentions - KIM, Dan J. (Institutional Knowledge at Singapore Management University, 2003)
There is little research on trust and satisfaction in the electronic commerce from a longitudinal (pre- and postpurchase) perspective. Based on previous frameworks and theories, this study developed a combined model of consumer trust and satisfaction in the context of Internet shopping. From the valance framework and expectation-confirmation theory, several prepurchase and post-purchase factors such as risk, benefit, consumer trust, expectation, confirmation, and satisfaction are investigated as research variables affecting consumer repurchase intention. The results of the study show that trust is the strongest predictor of the consumer’s purchase intention. In addition, as in traditional consumer satisfaction studies, it holds true in electronic commerce consumer behavior studies that the consumer’s satisfaction is still the critical determinant to its consequence, i.e., willingness to repurchase.